Design and Build a Fall Detection Monitoring System for the Elderly Using an Accelerometer - Siti Norhabibah; Wahyu Andhyka; Diah Risqiwati (JOINCS (Journal of Informatics, Network, and Computer Science), 2017)
Elderly is a last transitional period of human life. Decrease or disappearance of organ function such as loss of balance, reduced vision and hearing cause the elderly often fall. The limited physical ability of them requires supervision. Supervision is necessary to avoid undesirable thing occurs. Here, a tool called accelerometer can be used to supervise and monitor whether the fall incident occurs or not to the elderly. In this study, the magnitude of the acceleration in x, y, and z axes of the accelerometer sensor is processed into a total value of acceleration. Then the value will be compared with the lower threshold value and the higher threshold value. After that the total value of the acceleration is compared again with the threshold value of the total value orientations. The total value of acceleration is used to distinguish between regular activity and falling. The results of this study indicate that the system developed has the sensitivity values of 89% and specificity of 98%.